A DFTB study on the electronic response of encapsulated DNA nucleobases onto chiral CNTs as a sequencer - Seyyed Mostafa Monavari; Nafiseh Memarian (Scientific Reports, 2024)
Abstract Sequencing the DNA nucleobases is essential in the diagnosis and treatment of many diseases related to human genes. In this article, the encapsulation of DNA nucleobases with some of the important synthesized chiral (7, 6), (8, 6), and (10, 8) carbon nanotubes were investigated. The structures were modeled by applying density functional theory based on tight binding method (DFTB) by considering semi-empirical basis sets. Encapsulating DNA nucleobases on the inside of CNTs caused changes in the electronic properties of the selected chiral CNTs. The results confirmed that van der Waals (vdW) interactions, π-orbitals interactions, non-bonded electron pairs, and the presence of high electronegative atoms are the key factors for these changes. The result of electronic parameters showed that among the CNTs, CNT (8, 6) is a suitable choice in sequencing guanine (G) and cytosine (C) DNA nucleobases. However, they are not able to sequence adenine (A) and thymine (T). According to the band gap energy engineering approach and absorption energy, the presence of G and C DNA nucleobases decreased the band gap energy of CNTs. Hence selected CNTs suggested as biosensor substrates for sequencing G and C DNA nucleobases.